DMD/BMD prenatal diagnosis and treatment expectation in a single centre in China for 15 years - Xingjian Zhong; Siying Cui; Lina Liu; Yuxia Yang; Xiangdong Kong (BMC, 2021)
Abstract Objective DMD/BMD prenatal diagnosis for 931 foetuses. Background DMD is the most common fatal X-linked recessive muscular disease. There is no effective clinical treatment method at present. Accurate gene diagnosis and prenatal diagnosis technology are important ways for early detection, early prevention and early treatment. Methods A total of 931 prenatal diagnoses were performed for pregnant women with a definite family history of DMD or a history of DMD childbirth between 2005 and 2019. This report may be considered the largest DMD prenatal diagnosis report in a single centre worldwide. Multiple ligation-dependent probe amplification (MLPA) and next-generation sequencing were used in combination. Techniques and short tandem repeat (STR) linkage analysis were used to determine the location of the DMD gene mutation in the pregnant woman and then to detect the DMD gene in the foetuses. Results There were 872 families in our study. Among all 931 foetuses, 20.73% (193/931) were males expected to develop DMD and 16.33% (152/931) were female carriers. In addition, gonadal mosaicism was observed in 5 mothers, and gene recombination was identified in three foetuses. The results of the prenatal diagnosis were consistent with the results of the CPK analysis, and the results of the prenatal diagnosis were 100% accurate. Conclusions MLPA and Sanger sequencing, when combined with STR linkage analyses, can provide an accurate and rapid prenatal diagnosis. Due to the high de novo rate, prenatal diagnosis and genetic counselling should be given great attention.